A pilot study of temsirolimus and body composition. Issue 4 (27th July 2013) - Veasey-Rodrigues, Heloisa; Parsons, Henrique A.; Janku, Filip; Naing, Aung; Wheler, Jennifer J.; Tsimberidou, Apostolia M.; Kurzrock, Razelle
Abstract : Purpose: Body weight and composition play a role in cancer etiology, prognosis, and treatment response. Therefore, we analyzed the weight, body composition changes, and outcome in patients treated with temsirolimus, an mTor inhibitor that has weight loss as one of its side effects. Patients and methods: Sixteen patients with advanced solid tumors treated with temsirolimus were studied; body composition was evaluated utilizing computerized tomography images. Sarcopenia was defined as skeletal muscle index lower than 38.5 cm 2 /m 2 for women and 52.4 cm 2 /m 2 for men. Results: Five of 16 patients (31 %) were men; median age, 60 years. Forty‐four percent (7/16) of patients were sarcopenic. Fatigue, anemia, hyperglycemia, and hyperlipidemia were common. Baseline sarcopenia and body composition did not correlate with worse toxicity or treatment outcome. However, there was a trend for greater loss of adipose area ( p = 0.07), fat mass ( p = 0.09), and adipose index ( p = 0.07) for patients with grade 3 or 4 toxicities versus those with grade 1 and 2 side effects. Conclusion: Patients with higher grade toxicities tended to lose more body fat, suggesting a possible end‐organ metabolic effect of temsirolimus. These observations merit exploration in a larger cohort of patients.